Conceptualizing Islamic Social Enterprise (ISE) from Islamic Perspective - Muhammad Iqmal Hisham Kamaruddin; Sofiah Md Auzair (International Journal of Management, Accounting and Economics, 2024)
The developments of social enterprise (SE) concept around the world have significantly impacted Islamic organizations’ behavior and operation. Due to SE concept where both social and economic objectives are combined in a single entity, it has increased the complexity of Islamic organizations’ operation. This is vital in maintaining sustainability and offering more contribution toward people especially Muslims society around the world. Islamic organizations that adopted SE concept are known as Islamic Social Enterprise (ISE). With the various types of ISE economics activities and different approaches in legal formation, there are issues arising in relation to its refined and definite concept. The same issues also can be found in the studies related to social enterprise (SE). Therefore, this study attempts to conceptualize the definition of ISE by discussing its objectives specifically from Islamic perspective. This study will enrich the literature on ISE by providing its alternative concept from the Islamic perspective.